2018
DOI: 10.1039/c8ob02754d
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic enantioselective synthesis of acyclic pyrimidine nucleosides by aza-Michael reaction

Abstract: Organocatalytic enantioselective synthesis of acyclic pyrimidine nucleosides was achieved by the aza-Michael reaction of pyrimidines as N-centered nucleophiles to α,β-unsaturated aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…As the first choice, we selected the widely recognized Hayashi-Jørgensen catalyst AM1 due to its well-established reputation for exhibiting high generality and applicability, particularly in organocatalytic CÀ N bond formation of enals. [29,[39][40][41][42][43] Contrary to expectations, the catalyst performance was unsatisfactory, regardless of the presence of benzoic acid as a cocatalyst (Table 1, entry 1-2). This outcome strongly indicated that the activation of the ketone functionality on reagent 2 a was a fundamental requirement for achieving at least moderate yield.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…As the first choice, we selected the widely recognized Hayashi-Jørgensen catalyst AM1 due to its well-established reputation for exhibiting high generality and applicability, particularly in organocatalytic CÀ N bond formation of enals. [29,[39][40][41][42][43] Contrary to expectations, the catalyst performance was unsatisfactory, regardless of the presence of benzoic acid as a cocatalyst (Table 1, entry 1-2). This outcome strongly indicated that the activation of the ketone functionality on reagent 2 a was a fundamental requirement for achieving at least moderate yield.…”
mentioning
confidence: 65%
“…In our pursuit of optimizing the yield and enantioselectivity of product 3 a , we conducted a screening of various catalysts in the domain of iminium catalysis, focusing on enals 1 a – w as the substrate class. As the first choice, we selected the widely recognized Hayashi‐J ø rgensen catalyst AM1 due to its well‐established reputation for exhibiting high generality and applicability, particularly in organocatalytic C−N bond formation of enals [29,39–43] . Contrary to expectations, the catalyst performance was unsatisfactory, regardless of the presence of benzoic acid as a cocatalyst (Table 1, entry 1–2).…”
Section: Figurementioning
confidence: 99%